2019
DOI: 10.1007/s10840-019-00625-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ventricular tachycardia substrate resolution with a novel omnipolar high-density mapping catheter: the omnimapping study

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Prior clinical studies have demonstrated the role of MPM catheters for the treatment of atrial and ventricular arrhythmias in the presence of structural heart disease 19–22 . However, few studies have compared multipolar with conventional PbyP mapping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior clinical studies have demonstrated the role of MPM catheters for the treatment of atrial and ventricular arrhythmias in the presence of structural heart disease 19–22 . However, few studies have compared multipolar with conventional PbyP mapping.…”
Section: Discussionmentioning
confidence: 99%
“…A novel feature of the HDG catheter is an ability to create bipolar EGMs at orthogonal directions to account for the direction of wavefront propagation 4 . Previous studies have shown that the electrode orientation in relation to wavefront activation is in part responsible for the bipolar EGM 21,26 . If wavefront propagation is orthogonal to the orientation of the bipole it may be subject to a cancellation effect 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo, activation occurs in 3D, and it is unlikely that this scenario is relevant in clinical cases (isoelectric EGM without an intrinsic amplitude). 25 Additionally, repeated sampling in a region of interest also overcomes this limitation, as the catheter orientation varies with each manipulation, increasing the probability of detecting a larger local EGM.…”
Section: Bipole Orientationmentioning
confidence: 99%
“…This provides a more efficient point acquisition and greater VT substrate definition of the scar BZ so facilitating conduction channel identification and quantification, which are both important surrogates for ablation strategy. 16 Our group has subsequently shown that VT mapping with the HD GRID has a significant positive impact on the long-term outcomes of VT ablation (paper in press).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a wide range of substrate ablation strategies have been developed over the years from scar homogenization to scar dechanneling or core isolation. Many of these topics have been the focus of a number of prior reviews, some published by our group 15,16 …”
Section: Introductionmentioning
confidence: 99%